Kajian Yuridis Pemanggilan Notaris Sebagai Saksi Terkait Perkara Penipuan dan Penggelapan Di Direktorat Reserse Kriminal Umum Polda Sumut - Tambunan, Poltak M.; Minin, Darwinsyah; Barus, Utary Maharani (Universitas Medan Area, 2021)
Notary public with an officiating trusted in practicing nowadays has got many attention paid for there are many notary forced to come forward police officer, points related with presumably violated to the deed he/she produced. Provided calling-on Notary by police officer, it is noted in differently status either as official witness or as suspected. Notary as public official is at once also stated professional, in hold the duty his position may play very important role in helping public there at once promote certainty rules. Official of notary public in reality, the appointment is under government also to dismiss out. In conducting the duties, notary is officiating the state charges, and on the deed he/she produced, namely known as minute ( original document in deed ) is perhaps categorized a state document. Public official is any officiating that government appoint and also to terminate under governmental power. In hold the duties is given authority and obligatory to serve public in certainty matters, for in the line of working is conducting as well as governmental authority with authority. Although notary is a public official that government appoint it up and terminate, but in hold the work, a notary is not governmental employee that got salary from government. The regulations No. 8 of 1974 regarding the principles of governmental employees is not applicable to the notary official.